Social assistance beneficiaries or workers? The ambiguity of labor integration proposed by the ProEmpleo program in Chiloé (Chile) (Revista LIDER, 2020)
The emergency job program ProEmpleo, implemented on Chiloé Island since the outbreak of the salmon crisis in 2008, has become an alternative labor market, generating forms of underemployment and perpetuating professional uncertainty. This paper proposes the figure of the precariat of the "poorworker", an individual who, only after being recognized as in a vulnerable situation by the institutions, has access to a work quota. This article discusses the ways and possibilities of professional integration of this population by addressing the experience of statutory ambiguity between social assistance beneficiaries and worker, in which tension marked by the emergence of a labor consciousness and empowerment through work takes place.